The effects of english curriculum achieved by teachers of sixth grade from Nuevo Vedado and Varital Elementary Schools, David, Chiriquí, 2010 - Aguirre Guerra, Michelle Lisbeth (UDELAS, 2010)
Our research aims to provide strategies to strengthen the study and independent learning and continuing application in the entity intends to assist in the ongoing education reform process and thereby contribute to improving the quality of education that is offered in the entity.